О сезонной смене шерстного покрова у белки-телеутки (Sciurus vulgaris exalbidus Pall.) - Крыжановский, В.И. (Вестник зоологии, 1970)
Moult was studied in.Sciurus vulgaris exalbidus Pall, kept in open-air cages. As a result of observations, it was established that the spring moult spreads from head to tail and ventro-dorsally and the autumn one — from the tail to head and dorso-ventrally. However, this regularity manifests only as a genera! tendency and deviations from il are usual.
The spring moult occurs with a gradually accelerating rate. Animals beginning the moult later, are subjected to it more intensively. The shedding of winter fur is sometimes delayed, in spite of growing the summer one under it and vice versa, the summer fur on some parts of the body (sacrum, femurs) can fall even before the winter one begins growing, which apparently, indicates that some different factors are responsible for the regulation of these two processes.
The spring moult lasts for 2—3 months (from April to June), the autumn one — 40—42 days (from the middle of September up to the end of October). Growing of tail hair begins from its end, from the ventral side and spreads to the root